1983
DOI: 10.1021/ac00263a028
|View full text |Cite
|
Sign up to set email alerts
|

Determination of long-chain alkylbenzenes in environmental samples by argentation thin-layer chromatography/high-resolution gas chromatography and gas chromatography/mass spectrometry

Abstract: 8) Schutjes, C. P. M.; Vermeer, E. A.; Rijks, J. A.: Cramers, C. A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The LABs have been found to be significant components of municipal wastes derived from sewage sludges (Takada & Ishiwatari 1987). They are persistent in the environment and are regarded as complimentary to the faecal sterols as wastespecific markers of urban or domestic sewage pollution (Eganhouse et al 1983b;Murray et al 1987).…”
Section: Long-chain Alkylbenzenesmentioning
confidence: 99%
“…The LABs have been found to be significant components of municipal wastes derived from sewage sludges (Takada & Ishiwatari 1987). They are persistent in the environment and are regarded as complimentary to the faecal sterols as wastespecific markers of urban or domestic sewage pollution (Eganhouse et al 1983b;Murray et al 1987).…”
Section: Long-chain Alkylbenzenesmentioning
confidence: 99%
“…TABs are believed to have over 80 000 possible congeners that make up a complex suite of largely unresolved chromatographic peaks (13). TABs are believed to have over 80 000 possible congeners that make up a complex suite of largely unresolved chromatographic peaks (13).…”
Section: Introductionmentioning
confidence: 99%
“…The LABs have been synthesized since the mid 1960s in the production of linear alkylbenzenesulfonates (LAS), the most widely used anionic surfactants. LABs are found as unsulfonated residues in detergents along with the LAS (34). Although it is believed the LABs do not represent an environmental threat (34), they degrade much more slowly than LAS (3) and accumulate in marine sediments (35).…”
Section: Linear Alkylbenzenesmentioning
confidence: 99%
“…LABs are found as unsulfonated residues in detergents along with the LAS (34). Although it is believed the LABs do not represent an environmental threat (34), they degrade much more slowly than LAS (3) and accumulate in marine sediments (35). For this reason and owing to the fact that LABs are always present along with the alkylbenzene sulfonates in the common domestic and industrial detergents, they have been suggested as specific molecular markers of anthropogenic waste contamination (2,3,36,37).…”
Section: Linear Alkylbenzenesmentioning
confidence: 99%
See 1 more Smart Citation